Global inflation synchronization - Jongrim Ha; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSİAD Economic Research Forum (ERF), 2019)
We study the extent of global inflation synchronization using a dynamic factor model in a large set of countries over a half century. Our methodology allows us to account for differences across groups of countries (advanced economies and emerging market and developing economies) and to analyze commonalities in inflation synchronization across a wide range of inflation measures. We report three major results. First, inflation movements have become increasingly synchronized internationally over time: a common global factor has accounted for about 22 percent of variation in national inflation rates since 2001. Second, inflation synchronization has also become more broad-based: while it was previously much more pronounced among advanced economies than among emerging market and developing economies, it has become substantial in both groups over the past two decades. In addition, inflation synchronization has become significant across all inflation measures since 2001, whereas it was previously prominent only for inflation measures that included mostly tradable goods.
Keywords: E31; E32; F42; 330; Global inflation; synchronization; dynamic factor model; advanced economies; emerging markets; developing economies